Role of HLA alleles polymorphism in systemic lupus erythematosus: A prospective study from North India - Ranjan S. Rana; Bitan Naik; Mahima Yadav; Usha Singh; Anup Singh; Shailja Singh (Indian Journal of Pathology and Microbiology)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disorder and has complex etiopathogenesis. The most appropriate hypothesis states that genetic susceptibility in the presence of environmental risk factors predisposes to SLE. HLA class II alleles are critical to immune response and are highly polymorphic. Various alleles in HLA-DR and -DQ regions were analyzed in SLE patients and healthy controls to see their role in susceptibility or protection to SLE. Materials and Methods: This was a prospective observational study, in which a total of 100 SLE patients and 100 controls were analyzed. HLA typing was done by polymerase chain reaction (PCR)-sequence-specific oligonucleotide (SSO) method (SSO probe). Results: DRβ1*0301 was significantly increased in SLE patients when compared to controls and had the highest odds ratio. Other risk factor alleles found to be increased were DRβ1*0701, DQβ1*0202, and DQβ1*0301, which had a significant positive association with SLE, suggesting their role in susceptibility to SLE. In contrast, DRβ1*0401, DRβ1*1401, DRβ1*1404, DRβ1*1501, DQβ1*0501, and DQα1*0201 showed statistically significant reduction in SLE patients, while these were much more common in controls, suggesting their protective role. Conclusion: This study is only the second study in patients from North India and it determines the role of DRβ1*0301, DRβ1*0701, DQβ1*0202, and DQβ1*0301 alleles as risk factors in SLE patients.